Long-term participation tax rates - Charlotte Bartels (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Generous income support programs as provided by European welfare states have often been blamed to reduce work incentives for the lowskilled and to increase durations of unemployment. Standard studies measure work incentives based on annual income concepts. This paper analyzes work incentives inherent in the German tax-benefit system when extending the time horizon to three years (long-term). Participation tax rates are computed for 1-year and 3-year periods 1995-1997 and 2005-2007 to reveal potential effects of the labor market and tax reforms between 1999 and 2005. The results show that participation tax rates are significantly lower over a 3- year period pointing at an overestimation of the disincentives by standard measures. Reforms reduced participation tax rates, particularly for singles and low-income individuals.
Keywords: H31; J65; 330; welfare; work incentives; unemployment; unemployment insurance